Descriptions of three new species of Dzhanokmenia (Hymenoptera: Eulophidae) from China - Li, Qin; Wang, Chao; Hu, Hong-Ying; Kostjukov, Viktor V.; Salle, John La; Zhu, Chao-Dong (Zootaxa, 2016)
Three new species of Dzhanokmenia Kostjukov (Hymenoptera: Eulophidae: Tetrastichinae), D. muleica Li, Wang & Hu sp. n., D. karamayica Li, Wang & Zhu sp. n. and D. gobica Li, Wang & Zhu sp. n. from Xinjiang Uyghur Autonomous Region of China are described and illustrated. A key to all known species of the genus is provided.